Disordered granular crystals - Martínez Ulloa, AJ (2018)
Phenomena related to disorder and nonlinearity have been studied in many different context in physics, from condensed-matter physics to optics, with a substantial potential for applications. In particular, in mechanical systems, one can think of "smart" materials that adapt their properties, such as thermal conductivity or wave-transmission properties, depending on external stimuli, such as changes in pressure. It is the aim of this dissertation study transport and localization properties of one-dimensional disordered and quasiperiodic granular crystals as a function of an external precompression on the system. To archive this, we first study the scattering problem of a single impurity in a homogeneous granular chain and we demonstrate the existence of analogs to quantum resonances.